Cattle feeding in the Great Plains: economic and environmental impacts of cattle performance and disease management - Day, Merri Elizabeth (My University, 2025)
The United States Roundtable for Sustainable Beef (USRSB) is credited with developing a framework that provides specific targets for achieving sustainability throughout all sectors of the U.S. beef industry. Livestock operations have been identified as important contributors to greenhouse gas emissions, and the U.S. beef industry is under considerable pressure to reduce its environmental footprint, specifically within the feedyard sector. The USRSB aims to reduce feedyard greenhouse gas emissions by 10% per pound of beef produced by 2030. The USRSB also identifies animal health and well-being, which includes assurance of proper veterinary care, as a top priority for beef feedyards. In beef cattle feedyards, challenges related to animal health and disease management are compounded by space and density, and even the most treatable illnesses can have considerable harmful effects on both herd health and economic returns. Innovations in feeding technologies such as growth implants and feed additives have shown potential for reducing greenhouse gas emissions. Advancements in veterinary diagnostics and use of antimicrobials have proven effective in improving outcomes for diseased cattle in feedyards. However, economic viability of these management practices is paramount to achieving feedyard sustainability goals set forth by the USRSB. The first study examines how alternative cattle feeding management decisions impact both net returns and greenhouse gas emissions. We use established procedures to estimate the effects of changes in mortality and growth implant protocols on feedyard net returns. We then propose new methods for estimating concurrent impacts to feedyard greenhouse gas emissions. Using operational feeding data, we find that reducing mortality consistently increases net returns while reducing greenhouse gas emissions intensity. Additionally, our findings indicate that using two growth implants compared to one has potential for simultaneous improvement of both net returns and greenhouse gas emissions intensity. The second study estimates net returns from feedyard cattle identified with acute interstitial pneumonia (AIP) ante-mortem and post-mortem. A decision tree framework is implemented to estimate net returns for cattle that finished with their cohort, were culled, or died following an AIP diagnosis. Using comprehensive data, we find that economic outcomes vary across sex, placement weight, and number of AIP treatments. Findings generally indicate that expected returns from treating cattle identified with AIP are favorable to estimated returns from culling. The third study examines predictors of terminal outcomes for feedyard cattle diagnosed with AIP ante-mortem. Using comprehensive data, mixed-effects logistic models are employed to estimate the probabilities of first AIP treatment failure and failure to finish for cattle treated at least once for AIP. Findings from this analysis indicated that sex, weight, AIP treatment timing, and prior bovine respiratory disease treatment were significantly associated with the probability of first AIP treatment failure and probability of failure to finish. Building upon findings from the second and third studies, we develop a spreadsheet-based decision aid to support the management of feedyard cattle identified with AIP. Following methods described in the second study, the decision aid prepares a comparison of expected returns from treating an animal compared with estimated returns to culling the animal without AIP treatment, along with probabilities of AIP treatment outcomes as described in the third study.
Keywords: Agriculture; Economics; Livestock